PERANCANGAN SISTEM INFORMASI PARKIR TERINTEGRASI DENGAN QR CODE DI UNIVERSITAS ABC - Salwanur Karimah, Agidia; Ardelina, Shakila; Dwinta Putri Muharram, Nayla; Niqotaini, Zatin (TEKNOFILE : Jurnal Sistem Informasi, 2025)
Advances in information technology have enabled improvements in service systems such as campus parking management. QR Code is a two-dimensional technology that can be used to store large amounts of data and is easily accessible by scanners due to its flexibility and speed of integration. Conventional campus parking systems, which require the use of tickets and manual recording, often lead to errors and waste. Parking information systems that use QR Code are connected to the campus user database. Advances in information technology have enabled improvements in service systems such as campus parking management. QR Code is a two-dimensional technology that makes large amounts of data easily accessible by scanners. Due to its flexibility and speed of integration, this technology is an alternative to barcodes. Errors and waste often occur due to the old campus parking system, which requires tickets and manual recording. Parking information systems are connected to the campus user database via QR Code.